PERBANDINGAN ANGKA KEJADIAN MIOPIA ANTARA MAHASISWA INFORMASIKA DAN ILMU KELAUTAN UNIVERSITASSAM RATULANGI MANADO - Matheos, Merina; Rares, Laya M.; Saerang, J. S. M. (e-CliniC, 2015)
Abstract: The most obvious risk factors that lead to myopia is associated with a close-range activity, such as reading, writing, using the computer and playing video games. Along with the progress of the current students learning styles, students are required to seek as much information and the process of finding information easier by the existing technologies, which is the use of computers. Especially in student Informatics, computer is the main medium of learning. As with the system of Marine Science student that learn through field practice. On the other hand, commonly, students tend to perform activities at close range and supported by genetic factors that influence the incidence of myopia or nearsightedness. Objective: This study aims to determine differences in the incidence of myopia among the students of Informatics and Marine Sciences University of Sam Ratulangi. Methods: This study is analytical observational with cross-sectional approach by usingconsecutivesampling. Results: From the results of this study showed that there was no significant difference in the incidence of myopia among Informatics students and Marine Science students (P = 0.056) with the use of Z test. Conclusion:There was no significant difference in the incidence of myopia among Informatics students and Marine Science students.Keywords: myopia, students, informatics, marine sciencesAbstrak: Faktor risiko paling nyata yang menimbulkan miopia adalah berhubungan dengan aktivitas jarak dekat, seperti membaca, menulis, menggunakan komputer dan bermain video game. Seiring dengan kemajuan gaya belajar mahasiswa saat ini, mahasiswa dituntut untuk mencari informasi sebanyak-banyaknya dan proses mencari informasi semakin dipermudah dengan teknologi-teknologi yang ada, salah satunya adalah dengan penggunaan komputer. Khususnya pada mahasiswa Informatika, komputer merupakan media utama belajar. Lain halnya dengan mahasiswa Ilmu Kelautan yang sistim pembelajarannya melalui praktek lapangan. Di sisi lain, pada umumnya mahasiswa zaman sekarang cenderung melakukan aktifitas jarak dekat serta ditunjang dengan faktor keturunan yang berpengaruh dalam terjadinya kejadian miopia atau rabun jauh. Tujuan:Penelitian ini bertujuan untuk mengetahui perbedaan angka kejadian Miopia antara Mahasiswa Informatika dan Ilmu Kelautan Universitas Sam Ratulangi Manado.Metode:Penelitian ini bersifat analitik observasional dengan pendekatan potong lintang (cross sectional) dan cara pengambilan sampel menggunakan konsekutif sampling.Hasil: Dari hasil penelitian ini didapatkan bahwa tidak ada perbedaan bermakna kejadian miopia antara Mahasiswa Informatika dan Mahasiswa Program Studi Ilmu Kelautan (P=0,056) dimana menggunakan uji Z. Simpulan: Tidak ada perbedaan bermakna kejadian miopia antara Mahasiswa Informatika dan Mahasiswa Program Studi Ilmu Kelautan.Kata kunci: miopia, mahasiswa, informatika, ilmu kelautan